TINGKAT KEPUASAN KONSUMEN WHAT’S UP CAFE MANADO - Virjinia ., Tulungen; Theodora Maulina Katiandagho; Agnes Estephina Loho (AGRI-SOSIOEKONOMI, 2019)
The purpose of this study was to determine the level of consumer satisfaction What's Up Cafe Manado regarding products, prices, places, and services. This research was conducted for 2 months from February to March 2019. Determination of the sample using accidental sampling technique. Data collected in this study are primary data and secondary data. Primary data were collected from direct interviews with 30 respondents (consumers) using a questionnaire with a Likert scale.Secondary data were obtained from local bookstores and the internet. From the internet using Google Scholar to get books, scientific journal articles and theses from other universities related to research topics on the level of consumer satisfaction. The results showed that the level of consumer satisfaction of What’s Up Cafe Manado overall was classified as very satisfied by 82.04%. In detail, the level of customer satisfaction for What's Up Cafe for the very satisfied category was 84.45% for product variables, 83.99% for prices, and 80.33% for places. For the satisfied category, the service variable is 79.99%.*eprm*